The role of information literacy competence and higher order thinking skills to develop academic writing in Science and Engineering learners - B. Kranthi Kumari (Laureate Education Inc, 2016)
The English syllabus for learners pursuing engineering courses includes teaching writing as one of the objectives. Learners who enroll for these courses are not equipped with the general writing skills that they should have mastered at the entry level. In this context, a study was organized to develop academic writing skills of the undergraduate learners who are pursuing engineering courses.  The study focused on raising awareness in the learners of the nature and characteristics of academic texts in order to develop academic writing skills. The study also emphasizes that involving the learners in the cognitive processes of writing that include defining the rhetorical problem, identifying the rhetorical situation, the audience and setting goals for writing, planning for the text by generating and organizing ideas is necessary. The study further suggests that discussions between learners and teachers regarding the construction of a text and the way language works in various text types facilitates better writing.